2006
DOI: 10.1097/01.ccm.0000208359.74623.1c
|View full text |Cite
|
Sign up to set email alerts
|

Early ventilation and outcome in patients with moderate to severe traumatic brain injury*

Abstract: Arrival hypercapnia and hypocapnia are common and associated with worse outcomes in intubated but not spontaneously breathing patients with traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 79 publications
2
121
1
3
Order By: Relevance
“…Nonneurological organ dysfunction is an important predictor 66 Early physiological derangements are known to be associated with worse outcomes, and their timely correction could influence recovery. [67][68][69] Consistent with this notion, one randomized controlled trial demonstrated that pre-hospital rapid sequence intubation (RSI) by paramedics increased the proportion of TBI patients with a favourable neurological recovery. 14 Pre-hospital RSI was routine practice in Southern Alberta even before the time period assessed in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Nonneurological organ dysfunction is an important predictor 66 Early physiological derangements are known to be associated with worse outcomes, and their timely correction could influence recovery. [67][68][69] Consistent with this notion, one randomized controlled trial demonstrated that pre-hospital rapid sequence intubation (RSI) by paramedics increased the proportion of TBI patients with a favourable neurological recovery. 14 Pre-hospital RSI was routine practice in Southern Alberta even before the time period assessed in this study.…”
Section: Discussionmentioning
confidence: 93%
“…35,36 Patients who are hyperventilated are more likely to be in a persistent vegetative state or require permanent assistance with activities of daily living if they survive their hospitalization. In contrast, investigators have shown that normocapnia in TBI is associated with less neurologic impairment and better functional independence.…”
Section: Hypocapnia In Tbimentioning
confidence: 99%
“…The possible detrimental impact of prehospital intubation is associated with the risk of hyperventilation and positive pressure ventilation. Hyperventilation (9) and hypoventilation (28,29) in intubated patients with TBI increase the mortality rate. Only targeted prehospital ventilation is associated with lower mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Positive pressure ventilation increases intrathoracic pressure, which reduces the venous return and decreases blood pressure and cardiac output. (10,22,28) Increased intrathoracic pressure can be retrogradely transmitted through the jugular venous system raising intracranial pressure as a result. (31) However, hyperventilation reduces ICP through vasoconstriction (17) and is recommended as a treatment in patients with acute brainstem herniation.…”
Section: Discussionmentioning
confidence: 99%